Morphometry of Villous Membrane of Placenta at high and low Altitudes - Saga, Zarmina Saga; Liaqat Ali Minhas, Liaqat Ali Minhas (Journal of Rawalpindi Medical College, 2009)
Background: This cross sectional study was designed to compare the histomorphological characteristics of human placenta at low and high altitudes, with special reference to villous membrane. It was a cross sectional comparative study, conducted at Anatomy department of Army Medical College Rawalpindi, from October 2002 to April 2003. Methods: Forty placentae were collected from normal cases at Rawalpindi (low altitude/ LA) and 40 were collected at Skardu (high altitude/HA). Samples of placental tissue were taken and processed. Histological study was done in H & E and PAS stained sections. Detailed morphology of terminal villi and villous membrane was studied. Thickness of villous membrane was measured which has not been mentioned in previous studies. Results: Mean value of villous membrane thickness in LA and HA groups was 2.188 + 0.023 m and 2.027 + 0.020 m respectively. The quantitative difference between mean thickness of villous membrane in LA and HA groups was statistically significant Conclusion: Thickness of villous membrane was significantly less in high altitude group probably showing adaptive changes to overcome the effect of reduced oxygen tension.